2018
DOI: 10.1038/s41375-018-0297-4
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell analysis identifies CRLF2 rearrangements as both early and late events in Down syndrome and non-Down syndrome acute lymphoblastic leukaemia

Abstract: Deregulated expression of the type I cytokine receptor, CRLF2 , is observed in 5-15% of precursor B-cell acute lymphoblastic leukaemia (B-ALL). We have previously reported the genomic landscape of patients with CRLF2 rearrangements ( CRLF2 -r) using both whole genome and exome sequencing, which identified a number of potential clonal and sub-clonal genomic alterations. In this study, we aimed to assess when the CRLF2 -r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 57 publications
1
22
0
1
Order By: Relevance
“…In DS-ALL, recent studies of sub-clonal and single-cell evolution of changes in leukemic ALL blasts have identified signaling activators (CRFL2-rearrangements, JAK2 mutations, RAS-MAPK mutations and iAMP21) as frequent events in primary and relapsed leukemic blasts (20,21,38). In particular, JAK2 and RAS mutations were found to be both acquired and lost in relapse samples in a mutually exclusive manner (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…In DS-ALL, recent studies of sub-clonal and single-cell evolution of changes in leukemic ALL blasts have identified signaling activators (CRFL2-rearrangements, JAK2 mutations, RAS-MAPK mutations and iAMP21) as frequent events in primary and relapsed leukemic blasts (20,21,38). In particular, JAK2 and RAS mutations were found to be both acquired and lost in relapse samples in a mutually exclusive manner (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Acute lymphoblastic leukemia (ALL) is the most common type of leukemia, and is characterized by uncontrolled proliferation of immature lymphoid cells [ 1 , 2 ]. Despite significant advances over the past few decades to develop treatments for ALL, ~ 25% of children and half of the adults do not respond to chemotherapy or relapse [ 3 5 ]. At present, the available treatment options for ALL include chemotherapy, antibody therapy and allogeneic bone marrow transplantation, and the treatment used depends on the stage of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Genomic studies have provided conflicting evidence regarding the role of CRLF2/IL7RA aberrations in leukemic evolution. Aberrant expression of the receptors may be clonal or subclonal, preserved or altered between diagnosis and relapse 7,[19][20][21] . Two mouse models suggest that under specific conditions, expression of CRLF2 and/or IL7RA may initiate BCP-ALL [22][23][24] .…”
Section: Introductionmentioning
confidence: 99%